Managing politics and Islam in Indonesia - Porter, Donald J. (RoutledgeCurzon, 2002)
This book examines the politics of Islam and the state in Indonesia over recent decades, during which time there has been a notable resurgence of Islamic political movements. It argues that after a period in the late 1980s and 1990s, when the state worked to bring religious authority and institutions within state-prescribed limits in order to support the official state ideology and political stability, there was a change whereby Suharto incorporated Muslim interests within the political system. One unintended consequence of this was to raise Muslims' political expectations and to mobilise Muslim political interests in the context of broadening 'pro-democracy' opposition which contributed to the downfall of Suharto's regime. Based on extensive original research, including interviews with participants, the book charts the shifts in relations between Islam and the Indonesian state over time, assessing the impact on other groups, and on the cohesion of Indonesia overall.